2017
DOI: 10.1016/j.precisioneng.2017.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Part accuracy improvement in two point incremental forming with a partial die using a model predictive control algorithm

Abstract: .Part accuracy improvement in two point incremental forming with a partial die using a model predictive control algorithm.Precision Engineering http://dx.doi.org/10. 1016/j.precisioneng.2017.02.006 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…The TPIF process ( Fig. 1b) developed by Matsubara [5] can improve the geometric accuracy of the manufactured components by using supporting dies [6]. By using dedicated solid dies, the TPIF process is less flexible than SPIF [7].…”
Section: Incremental Sheet Formingmentioning
confidence: 99%
“…The TPIF process ( Fig. 1b) developed by Matsubara [5] can improve the geometric accuracy of the manufactured components by using supporting dies [6]. By using dedicated solid dies, the TPIF process is less flexible than SPIF [7].…”
Section: Incremental Sheet Formingmentioning
confidence: 99%
“…Besides the preferred orientation and the relative thickness (t/D) of sheet metal, wrinkling is related to the stress ratio of deformation, the mechanical properties of the material, the geometric shape of the die, and the contact conditions between workpiece and die [25,26]. However, it is difficult to take account of all of these factors in a theoretical model.…”
Section: Theoretical Prediction Model For Sheet Plastic Instabilitymentioning
confidence: 99%
“…[9,12], wrinkling can still occur during sheet forming. To improve the precision and quality of forming of parts and effectively eliminate wrinkling instability, it is particularly important to obtain accurate predictions of the likelihood of wrinkling in the forming process [24][25][26]. Therefore, it is necessary to investigate the prediction of wrinkling of sheet metal during warm/hot hydroforming.…”
Section: Introductionmentioning
confidence: 99%
“…The defects were reduced by controlling the related parameters of the stress ratio. Based on the basic structure of a simple Model Predictive Control (MPC) algorithm designed for SPIF in previous work [7], an enhanced MPC algorithm had been developed especially for Two Point Incremental Forming (TPIF) with a partial die by Lu et al [8]. Radu et al [9] found that the accuracy error mainly comes from the springback of the part after the tool head and the holding device are unloaded.…”
Section: Introductionmentioning
confidence: 99%